#TITLE_ALTERNATIVE# - RIYADUS SHOLIHIN (NIM. 20207092), AGUS
Tools to be used to measure body weight and to measure gravity acceleration by using sensor LVDT is presented. By giving mass to load spot, ferro core (armature) at LVDT will be displace and generate the changing in voltage, This changing is used to convert voltage to weight. From the experiment, we get spring constant k=96,63 N/m with the sensivity of LVDT M=0,049 m/Volt. From linearity regression of the data experiment we get W = 4,5161 Vo + 4,1164. By comparing of weight measuring and counting we get error 7,545619 %, average of gravity acceleration is 9,32657 m/s2 with error 4,83082 %.